Sports Medicine - Open - Olney, Roger; McMillan, Steve
Sports Medicine - Open focuses on original research and definitive reviews in the field of sport and exercise medicine. The Journal includes medical and scientific research relating to: Sporting performance enhancement including nutrition, equipment and training Medical syndromes associated with sport and exercise Injury prevention and treatment Exercise for rehabilitation and health The application of physiological and biomechanical principles to specific sporting codes Key Points Articles published in Sports Medicine - Open will include a Key Points table. Please provide approximately three short, stand-alone lines/statements summarizing the key findings/implications of the paper. These should be provided after the Abstract under the heading 'Key Points’.